STRATEGI PENGEMBANGAN PARIWISATA BUMI SAKTI ALAM KERINCI KABUPATEN KERINCI, PROVINSI JAMBI (Suatu Pendekatan Analitical Network Process) - Azita Yeja Casimeira; I Gst. Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2016)
This research is about the management of which has been done and the development strategy of tourism “Bumi Sakti Alam Kerinci” province of Jambi Kerinci Regency. The purpose of this research is to know the application of management conducted by Disporaparbud based on management functions and define the priorities of the development strategy will be undertaken. Data collection is done by observation, interviews, library and documentation. Methods undertaken in this study analysed by Analitical chain processes are described qualitatively. The results of this research are indicating not optimal tourism management made during this so do not provide optimal development impact. This research resulted in the development of 6 strategies well for the optimal development of tourism kerinci. The strategy is calculated in advance does it weigh against management functions, and then produce a development strategy a priority in future development.